Perubahan Berat Badan Mencit (Mus musculus) Model Diabetes Melitus Tipe 1 yang Diterapi Ekstrak Alga Coklat Sargassum sp - Abdul M Ukratalo; Giovano Amahoru; Dodikrisno E Manery; Taufik Zuneldi; Victory O Pangemanan; Muhammad Fitrah Loilatu (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
In type 1 diabetes, when the body does not produce enough insulin or none at all. This causes blood glucose levels to remain high while the body's cells are starved for energy. As a result, the body turns to alternative energy sources, namely fat and muscle, leading to weight loss. Sargassum sp contains steroid, alkaloid, phenol, flavonoid, saponin and tannin compounds that can be antioxidant and antidiabetic. This study aims to determine changes in body weight of mice (Mus musculus) type 1 diabetes mellitus models treated with Sargassum sp. This study is an experimental study. Mice were divided into 6 groups, namely KN, K-, K+, P1, P2 and P3. Body weight was weighed on day 0, day 14 (post STZ induction) and day 28 (post drug administration). The data were analysed by ANOVA using SPSS program. The results showed that Sargassum sp extract can increase the body weight of DM mice.